2012
DOI: 10.1534/g3.112.004218
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Genes Required for Alternative Oxidase Production in the Neurospora crassa Gene Knockout Library

Abstract: The alternative oxidase (AOX) of Neurospora crassa transfers electrons from ubiquinol to oxygen. The enzyme is not expressed under normal conditions. However, when the function of the standard electron transport chain is compromised, AOX is induced, providing cells with a means to continue respiration and growth. Induction of the enzyme represents a form of retrograde regulation because AOX is encoded by a nuclear gene that responds to signals produced from inefficiently functioning mitochondria. To identify g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 95 publications
1
20
0
4
Order By: Relevance
“…Jab1/COPS5 was previously identified as an apoptosis inducing factor through modulation of mitochondrial BH3-domain containing protein BclGs [27]. A study found that in Neurospora crassa , three subunits of the COP9 were required to recover from deficiency of the alternative oxidase function, which is important for mitochondrial functions [28]. However, no follow up studies have been carried out for mammalian cells.…”
Section: Discussionmentioning
confidence: 99%
“…Jab1/COPS5 was previously identified as an apoptosis inducing factor through modulation of mitochondrial BH3-domain containing protein BclGs [27]. A study found that in Neurospora crassa , three subunits of the COP9 were required to recover from deficiency of the alternative oxidase function, which is important for mitochondrial functions [28]. However, no follow up studies have been carried out for mammalian cells.…”
Section: Discussionmentioning
confidence: 99%
“…In extant prokaryotes, AOX is limited to some α-proteobacteria (e.g., Novosphingobium aromaticivorans , [43]) and it is likely that AOX entered eukaryotic lineages via the ancient proteobacterial endosymbiont that gave rise to mitochondria [39]. AOX is also found sporadically in protists and fungi, in many cases within pathogenic organisms within these groups [44,45], but also within important non-pathogenic model systems such as the fungi Neurospora crassa [46] and Podospora anserina [47] Surprisingly, AOX is also present in many animal phyla, although clearly absent from vertebrates and arthropods [39,48]. The finding of AOX in the animal kingdom has spawned several recent studies in which the protein has been introduced into different vertebrates, as a means to study aspects of mitochondrial bioenergetics and signaling [4951].…”
Section: Alternative Oxidasementioning
confidence: 99%
“…A number of genes that affect aod-1 expression have been identified [ 23 , 28 , 29 ]. Two zinc cluster transcription factors, encoded by the aod-2 and aod-5 genes [ 23 , 30 ], bind constitutively as a heterodimer in the upstream region of the aod-1 gene and are required for the increased transcription of aod-1 that occurs under inducing conditions [ 19 , 30 , 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%